2021
DOI: 10.1186/s12889-021-10182-4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing inequities in maternal health among women living in communities of social disadvantage and ethnic diversity

Abstract: The response to the coronavirus outbreak and how the disease and its societal consequences pose risks to already vulnerable groups such those who are socioeconomically disadvantaged and ethnic minority groups. Researchers and community groups analysed how the COVID-19 crisis has exacerbated persisting vulnerabilities, socio-economic and structural disadvantage and discrimination faced by many communities of social disadvantage and ethnic diversity, and discussed future strategies on how best to engage and invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…Structural racism is “the totality of ways in which societies foster racial discrimination, through mutually reinforcing inequitable systems (in housing, education, employment, earnings, benefits, credit, media, health care, criminal justice, and so on) that in turn reinforce discriminatory beliefs, values, and distribution of resources, which together affect the risk of adverse health outcomes.” 19 (p1454) To improve perinatal health and COVID‐19 related outcomes for individuals from BIPOC communities, it is essential to identify and call out the structural racism that perpetuates these inequities 20,22,24 . The US health care system has been deeply strained by the COVID‐19 pandemic 25 . Lessons learned during this crisis can help improve care going forward and build resiliency during future public health emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…Structural racism is “the totality of ways in which societies foster racial discrimination, through mutually reinforcing inequitable systems (in housing, education, employment, earnings, benefits, credit, media, health care, criminal justice, and so on) that in turn reinforce discriminatory beliefs, values, and distribution of resources, which together affect the risk of adverse health outcomes.” 19 (p1454) To improve perinatal health and COVID‐19 related outcomes for individuals from BIPOC communities, it is essential to identify and call out the structural racism that perpetuates these inequities 20,22,24 . The US health care system has been deeply strained by the COVID‐19 pandemic 25 . Lessons learned during this crisis can help improve care going forward and build resiliency during future public health emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…These experiences can inform the algorithm previously mentioned and address the societal and structural racism occurring within healthcare and disadvantaged communities. [15] Comprehensive reviews have been performed to measure implicit bias in health care. A commonly used tool to assess implicit bias is the Implicit Association Test, which is available online.…”
Section: Discussionmentioning
confidence: 99%
“…For women with mental ill health, this should be further supported by a specialist perinatal mental health midwife [12]. Despite numerous publications [37,44,45] recommending the continuity of care(r) and services, COVID-19 disrupted this support for many families, who were left to navigate their maternity care through a screen on their laptop and/or birth alone amongst strangers. This mapping exercise showed that the work the perinatal mental health midwives were able to adapt allowed for care to continue in as normal a way as possible, thus combatting the issues arising in perinatal mental health due to COVID-19 (which were identified in the critical review).…”
Section: Summary Of Main Findingsmentioning
confidence: 99%